plz Answer me this full excercise
Attachments:
![](https://hi-static.z-dn.net/files/ded/182e7e610642adf0910caec6c833267b.jpg)
Answers
Answered by
3
1) x² + 9x + 18
= x² + 3x + 6x + 18
= x(x+3) + 6(x+3)
= (x+3) (x+6) ans.
2) x²- 10x + 9
= x² - x - 9x + 9
= x(x-1) - 9(x-1)
= (x-1) (x-9) ans.
3) y²+24y+144
= y²+ 12y+12y + 144
= y(y+12) +12(y+12)
= (y+12) ( y+12)
= (y+12)²
4) 5y²+5y-10
= 5y² + 10y - 5y - 10
= 5y(y+2) - 5(y+2)
= (y+2) (5y-5)
5) p²-2p-35
= p² - 7p + 5p -35
= p(p-7) + 5(p-7)
= (p-7) (p+5)
6) p²-7p-44
= p²-11p+4p - 44
= p(p-11) + 4(p-11)
= (p-11) (p+4)
๑•́ㅿ•̀๑) ᔆᵒʳʳᵞ
Anonymous:
ok
Answered by
1
Here is your answer mark
Attachments:
![](https://hi-static.z-dn.net/files/d10/53b1307ac347c06072b41c3689d4ec84.jpg)
Similar questions